Analysis of user's satisfaction on two wheeler segment performance with reference to chennai - Maran, K.; Anbazahagan, V. (university of Jaffna, 2014)
A Nations economy is well known from its transport system. For instant and rapid growth in economy, a well-developed and well-networked transportation system is essential. As India's transport network is developing at a fast pace, Indian Automobile Industry is growing too. Also, the Automobile industry has strong backward and forward linkages and hence provides employment to a large section of the population. Thus the role of Automobile Industry is very essential in Indian economy. The first signs of fragmentation of the market were visible even when the Indo-Japanese 100cc motorbikes were introduced. The motorcycle segment which had only 175,250 & 350cc bikes earlier was changed into 100cc, 175 and 350cc.in the 100cc category there was further fragmentation into two stroke engines and four stroke engines which really translated into two different levels of fuel efficiencies and durability. The key objectives of the study are to find out the Predictor Variables for Customers' Satisfaction towards Two Wheelers and to analyze the factors influencing on customer satisfaction towards the two wheeler brand. The sampling technique used in this study is convenience sampling. In this study, we presume that population size is finite and unknown; the formula was applied to know the sample size, and found the sample size is 575 among them 525 customers and 50 dealers meets the requirements. . The overall analysis of this study Hero Honda and Enfield has ranked equally in users satisfaction and rest of the two brands performance is somewhat satisfaction to the users of two wheelers in the emerging Indian two wheeler markets
Keywords: Nations economy; Transport; Growth